A systematic review and meta-analysis of spleen-preserving distal pancreatectomy with preservation or ligation of the splenic artery and vein. Issue 2 (April 2016) - Partelli, Stefano; Cirocchi, Roberto; Randolph, Justus; Parisi, Amilcare; Coratti, Andrea; Falconi, Massimo
Abstract: Introduction: Spleen-preserving distal pancreatectomy (SPDP) can be performed either by ligating (SPDP-VL) or preserving (SPDP-VP) the splenic vessels. Methods: A systematic review was performed, and standard PRISMA guidelines were followed. A literature search was conducted using Medline, PubMed and the Cochrane Central Register of Controlled Trials between January 1988 and May 2014. The article titles and abstracts were examined by two independent reviewers. Results: Thirteen non-randomized control trials were included in the meta-analysis. The pooled data included 667 patients who underwent SPDP. There were 209 patients in the SPDP-VL group and 458 patients in the SPDP-VP group. The risk of splenic infarction was significantly higher in the SPDP-VL group [20.88 vs. 2.09%; OR 11.89 (95% CI 4.33 to 32.70); p < 0.00001]. The rate of splenectomy as a result of splenic infarction was also statistically associated with SPDP-VL [7.69% vs. 1.36%; OR 3.87 (95% CI 1.05 to 14.26); p = 0.05)]. The surgical operative time was shorter in the SPDP-VL group than in the SPDP-VP group (mean difference 21.2 min), but this result was not statistically significant (95% CI −47.01 to −4.48; p = 0.11). The two procedures were comparable with respect to mean intraoperative blood loss and rate of pancreatic fistula. SPDP-VL did not influence the risk of developing perigastric collateral vessels and submucosal varices. Conclusions: SPDP-VL may result in a higher rate of splenic infarction and splenectomy than SPDP-VP. However, the low quality of the included studies does not lead to clear conclusions.